2019
DOI: 10.1016/j.scitotenv.2019.01.284
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the thermal comfort conditions of outdoor spaces in a university campus in Kuala Lumpur, Malaysia

Abstract: The rapid urban expansion in East-Asian cities has increased the need for comfortable public spaces. This study presents field measurements and parametric simulations to evaluate the microclimatic characteristics in a university campus in the tropical climate of Kuala Lumpur, Malaysia. The study attempts to identify the thermally uncomfortable areas and their physical and design characteristics while debating on the circumstances of enhancing the outdoor comfort conditions for the campus users. Simulations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 40 publications
0
33
0
2
Order By: Relevance
“…Ochoa et al investigated the suitability of combined optimisation criteria on window sizing methods for low energy consumption focusing on user visual comfort and performance [23]. Ghaffarianhoseini et al investigated the ability of vegetation [32] or unshaded courtyards [33] for contributing to outdoor thermal comfort based on various design configurations and scenarios. Rupp et al revealed that there is a gap in thermal comfort studies in relation to interdisciplinary research, and a connection with other related fields such as psychology, physiology, and sociologists could be of great asset for the development of an integrated research approach aiding a better understanding about perception and thermal comfort and its physiological and psychological dimensions [34].…”
Section: Performance Goals and Building Design Indicesmentioning
confidence: 99%
“…Ochoa et al investigated the suitability of combined optimisation criteria on window sizing methods for low energy consumption focusing on user visual comfort and performance [23]. Ghaffarianhoseini et al investigated the ability of vegetation [32] or unshaded courtyards [33] for contributing to outdoor thermal comfort based on various design configurations and scenarios. Rupp et al revealed that there is a gap in thermal comfort studies in relation to interdisciplinary research, and a connection with other related fields such as psychology, physiology, and sociologists could be of great asset for the development of an integrated research approach aiding a better understanding about perception and thermal comfort and its physiological and psychological dimensions [34].…”
Section: Performance Goals and Building Design Indicesmentioning
confidence: 99%
“…Referring to Table 3 , the comfort range and variables of PMV and PET are presented [ 66 ]. Earlier researchers reviewed outdoor thermal comfort using the PET [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. The PET has several advantages when used for outdoor conditions, as follows.…”
Section: Methodsmentioning
confidence: 99%
“…e microclimate affects the quality and efficiency of open spaces on university campuses [1] and can be significantly improved by appropriate planning [2][3][4]. In severe cold regions, the thermal comfort of outdoor spaces on campuses is affected by multiple climatic factors, such as sunlight, solar radiation, and wind speed.…”
Section: Introductionmentioning
confidence: 99%